Impact of Joint Line Level in Total Ankle Arthroplasty: Standard Techniques vs Patient-Specific Instruments - Alberto Arceri MD; Antonio Mazzotti MD, PhD; Federico Sgubbi MD; Simone O. Zielli MD; Elena Artioli MD; Laura Langone MD; Pejman Abdi MD; Cesare Faldini MD (Foot & Ankle Orthopaedics)
Background: Total ankle arthroplasty (TAA) is an effective treatment for severe end-stage ankle osteoarthritis (AO). Despite satisfactory results, range of motion (ROM) is still suboptimal compared to healthy ankles. This issue may stem from different conditions, and the difficulty in accurately restoring the height of the joint line may be one of them. Recent studies in TAA have demonstrated that an elevated joint line is associated with reduced postoperative ROM and poorer functional scores. To improve the accuracy of bone resection and implant positioning, the use of patient-specific instruments (PSIs) has been proposed. The aim of this study is to compare joint line height, ROM, and functional clinical outcomes between standard TAA and TAA using PSI. Methods: A retrospective analysis was conducted on a consecutive cohort of patients who underwent standard TAA and TAA with PSI between January 2020 and December 2022. Radiographic assessments, including measurement of joint line height ratio (JLHR) and ROM, were performed. The clinical outcome was assessed using the Forgotten Joint Score. Result: Fifty-one patients underwent standard TAA, whereas 13 received TAA with PSI. The mean JLHR preoperatively was 1.51 ± 0.24 and postoperatively was 1.56 ± 0.23 in the standard TAA group ( P  = .056). Conversely, the mean JLHR of PSI TAA group passed from 1.52 ± 0.19 to 1.41 ± 0.21 after TAA ( P  < .05). Although the postoperative joint line level in the PSI TAA group was lower compared with both the preoperative levels and the postoperative standard TAA group ( P  < .05), no significant differences were observed in ROM or clinical outcome scores at the mean 1-year follow-up. Conclusion: This study suggests that PSI may improve the accuracy of reestablishing this implant’s alignment closer to the native joint line. However, contrary to the study’s initial hypothesis, PSI was not associated with any difference in ROM or clinical outcomes compared with standard TAA technique. Additional factors including the prosthetic implant design, presence of heterotopic calcifications, soft tissue contracture, surgical technique, post-TAA tibial slope, and preoperative ROM may have a greater impact than joint line level. Level of Evidence: Level III, retrospective cohort study.